Interoception and body image in breast cancer patients: a mindfulness-based stress reduction protocol - Sebri, Valeria; Pizzoli, Silvia Francesca Maria; Marzorati, Chiara; Mazzocco, Ketti; Pravettoni, Gabriella (Frontiers in Psychology, 2024)
Breast cancer impairs physical and psychological well-being, even some years after treatments.Oncological treatments can strongly affect the body due to scars and breast(s) removal, for example, increasing symptoms of anxiety and depression. Psychological studies are effective in improving breast cancer survivors' emotions and behaviors through several approaches to interventions. Over years, the Mindfulness-Based Stress Reduction (MBSR) has been evaluated as an effective intervention to promote well-being in breast cancer survivors. The present study protocol aims to evaluate the effectiveness of a MBSR intervention in regulating interoceptive sensations, as the ability to be aware of inner sensations. Second, it seeks to identify changes in interoceptive feelings, mood, and body perception following the intervention. These changes will be evaluated across three data collection times to assess differences about emotions and body perception over time, focusing on their relevance for breast cancer survivors' well-being. Finally, the present study protocol aims to detect improvements in anxiety, depression, and body awareness, considering the potential positive impact of the MBSR approach on emotional well-being. Direction for future psychological intervention are given.